Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Produk Makanan Anchor di Kota Batam - Indriyani Indriyani; Nora Pitri Nainggolan (YUME : Journal of Management, 2025)
This study was conducted with the main objective to examine the influence of Brand Image, Product Quality and Trust on Purchasing Decisions of Anchor food products in Batam city. The population used in this study were consumers of PT Pundi Selaras Maju which included cake ingredient shops, supermarkets, pastries, and bakeries in Batam city as many as 143. Because the population was already known, the researcher used the Slovin formula in determining the number of samples with the purposive sampling method and obtained 105 consumers. The data obtained from the distribution of the questionnaire were then analyzed using data quality tests, classical assumption tests, influence tests, and hypothesis tests with multiple linear regression analysis methods using the SPSS version 26 application. The results of the multiple linear regression test identified that brand image contributed 10.1% to purchasing decisions, product quality 12.7%, and trust 45.6%. Tests conducted by applying the coefficient of determination (R2) obtained empirical evidence that brand image, product quality and trust as a whole were able to contribute 72.8% to purchasing decisions. Furthermore, the findings from the T-test and F-test analysis identified that brand image, product quality and trust, both partially and simultaneously, were independent variables proven to have a significant positive influence on purchasing decisions for Anchor food products in Batam City.Keywords: Brand Image, Product Quality, Trust, Purchasing Decisions